2016
DOI: 10.1177/1469540516668224
|View full text |Cite
|
Sign up to set email alerts
|

Moral conventions in food consumption and their relationship to consumers’ social background

Abstract: The purpose of this article is to examine how social background influences the way people evaluate and justify their food consumption. Theoretically, the article combines Bourdieu's theory of class-based practices with Boltanski and Thévenot's theory of situated judgement in order to better understand how social class and moral values are connected. Empirically, the article analyses how social class might constrain or enable certain types of justification for food consumption. Using quantitative data on Danish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 48 publications
(89 reference statements)
0
10
0
3
Order By: Relevance
“…This research indicates that while environmental concerns are the driving preferences of a relatively small group of highly reflexive and politically motivated consumers, other groups of consumers are motivated in their choices by other, individual concerns (Hjelmar, 2011;Grauel, 2014). A study by Stamer (2018) using the Convention approach found that people with high levels of cultural capital (defined by educational level, cultural activities and number of books in household), women, and older people, were all more likely to justify food purchases by referring to the common good (e.g. preserving the health of the environment) than other groups.…”
Section: The Holistic Perspective and Individualized Consumptionmentioning
confidence: 86%
See 2 more Smart Citations
“…This research indicates that while environmental concerns are the driving preferences of a relatively small group of highly reflexive and politically motivated consumers, other groups of consumers are motivated in their choices by other, individual concerns (Hjelmar, 2011;Grauel, 2014). A study by Stamer (2018) using the Convention approach found that people with high levels of cultural capital (defined by educational level, cultural activities and number of books in household), women, and older people, were all more likely to justify food purchases by referring to the common good (e.g. preserving the health of the environment) than other groups.…”
Section: The Holistic Perspective and Individualized Consumptionmentioning
confidence: 86%
“…Health concerns have been found to be linked to different orders of worth (Stamer, 2018;Andersen, 2011;Truninger, 2011). However, given the ubiquity of health concerns connected with the consumption of organic food as well as general food consumption (Ilmonen, 2011), our study does not assume that healthiness is tied to a specific regime of justification.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was mobilized extensively between the late 1990s and mid-2000s (see Murdoch & Miele, 2004;Wilkinson, 1997) to examine 'alternative food networks, coordination and governance of agro-food value chains, and the so-called "quality turn" in food production and consumption' (Ponte, 2016, p. 12). Convention theory is now experiencing something of a resurgence as new branches of agro-food research start to embrace it (including consumption, see Stamer, 2018;Thorslund & Lassen, 2017). Increased engagement has been accompanied by a proliferation in the ways that 'convention' and associated concepts of 'quality' and 'orders of worth' are used.…”
Section: Introductionmentioning
confidence: 99%
“…A importância atribuída pelos consumidores à qualidade dos alimentos tem aumentado nos últimos anos, envolvendo tanto atributos intrínsecos, como teores de gor dura e sal, quanto atributos extrínsecos, como sua origem geográfica e natureza do método de processamento, grau de susten tabilidade dos processos envolvidos, inocui dade do alimento (GRUNERT, 2005;STAMER, 2018).…”
Section: Introductionunclassified